Avaliação de dados epidemiológicos nas linfocintilografias de extremidades inferiores - Sant'Anna, Kleber Roberto (2017)
Introduction: Lymphedema is a clinical condition in which there is an accumulation of macromolecules in the interstitial space. As a result, it promotes water retention, consequently a failure in the formation or lymph drainage. Objectives: To access the images obtained from Computed Scintigraphy Chamber through a specific protocol of Lymphoscintigraphy and associate them to epidemiological data such as gender, age, educational level, socioeconomic status and prevalence of Lymphedema. Method: Epidemiological data were evaluated in a quantitative cross-sectional study comparing the diagnostic results for Lymphedema of the lower limbs using the Lymphoscintigraphy. They were correlated with gender, age, education level, family income and prevalence among the lower limbs at Hospital de Base in the last 10 years, 2006 to 2016. All patients clinically suspected of Lymphedema of the lower limbs were included and lymphoscintigraphic examinations of the upper limbs were excluded. Descriptive data were considered, and Fisher's exact test was used to correlate these variables considering alpha error of 5%. Results: A total of 430 patients were analyzed, 320(74.42%) were female and 110 (25.58%) male patients. Their age ranged from 10 to 90 years (mean = 48 years). A total 199 (46.27%) were positive findings and 231 (53.73%) negative. Among the images analyzed as positive; female patients were the majority, 183 (91.95%); Fisher's exact test p-value <0.001. When comparing patients with the first grade of high school with patients with complete college education, it was clear that Lymphedema was more prevalent in the first grade of high school, according to Fisher's exact test, p<0.0001. Comparing the second grade of high school with the ones with college education, it was observed that Lymphedema was more prevalent in those with high school; Fisher's exact test, p<0.0001. When comparing the wage gain from one to three minimum wages per month with three to five gains, five to seven and over seven salaries, a higher prevalence of Lymphedema was observed in the group of one to three salaries in relation to the others by Fisher's exact test, p<0.0001 in all evaluations. Comparing the salary range of three to five salaries with the salary range of five to seven and over seven monthly minimum wages, greater prevalence was observed in the range of three to five minimum wages; Fisher's exact test, p<0, 0.001 in both comparisons. The right lower limb presented 65 patients (32.66%), and 87(43.71%) unilateral left limb and 7 patients (23.63%), bilaterally were found. The left side was more prevalent than the right side; Fisher's exact test, p<0.01. Conclusions: Lymphedema is a public health issue that affects mostly women from lower cultural-educational socioeconomic status. One-sided onset can occur in the limb, but bilateral occurrence is frequent and Lymphoscintigraphy is useful in defining the diagnosis in cases of doubt.